2021
DOI: 10.1038/s41467-021-22900-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural coordination between active sites of a CRISPR reverse transcriptase-integrase complex

Abstract: CRISPR-Cas systems provide adaptive immunity in bacteria and archaea, beginning with integration of foreign sequences into the host CRISPR genomic locus and followed by transcription and maturation of CRISPR RNAs (crRNAs). In some CRISPR systems, a reverse transcriptase (RT) fusion to the Cas1 integrase and Cas6 maturase creates a single protein that enables concerted sequence integration and crRNA production. To elucidate how the RT-integrase organizes distinct enzymatic activities, we present the cryo-EM str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 71 publications
(56 reference statements)
1
23
0
Order By: Relevance
“…They also provide a basis for future biotechnological applications. Our structures, together with structures of group II intron maturases and CRISPR-associated RT ( 32 , 38 , 39 ), also fill important gaps in our knowledge of very diverse bacterial RTs.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…They also provide a basis for future biotechnological applications. Our structures, together with structures of group II intron maturases and CRISPR-associated RT ( 32 , 38 , 39 ), also fill important gaps in our knowledge of very diverse bacterial RTs.…”
Section: Discussionmentioning
confidence: 80%
“…Instead, its position in space is occupied by the first three helices of the helical domain of Ll- AbiK. The recent structures of the Cas6-RT-Cas1 fusion protein from Thiomicrospira showed that this protein also lacks the thumb subdomain ( 32 ). Therefore, loss or replacement of the thumb subdomain can occur to accommodate various functions of the polymerase domain.…”
Section: Resultsmentioning
confidence: 99%
“…This crosstalk between the different components of RT–CRISPR systems has been validated by the cryo-EM structure of a Cas6RTCas1–Cas2 complex from Thiomicrospira (Wang et al . 2021 ), in which the linking RT helix regulates both RT and Cas1 activities.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the RNA molecules could be ligated to either side of the first repeat of the array [ 57 ], which is consistent with the observed lack of orientation bias in the acquired spacers. On the other hand, the Cas1::RT-Cas2 complex from Thiomicrospira ligated RNA molecules to the CRISPR-containing DNA fragments in vitro but was unable to convert such intermediates to extended CRISPR arrays, suggesting that in vivo such conversion either requires additional factors, or that the cDNA synthesis must occur before the integration of prespacers into the CRISPR array, which should proceed in both orientations to explain the lack of spacer orientation bias [ 59 ].…”
Section: Spacer Acquisition In Type III Crispr-cas Systemsmentioning
confidence: 99%